Since we can't see your work, I'm afraid there is no way to do this. Sorry!leeyiu said:can u tell me if I have made any mistakes
leeyiu said:I know what's that ...
4a^2+4b^2+4C^2-4ab-4ac-4bc ... can u tell me if I have made any mistakes
leeyiu said:4a^2+4b^2+4C^2-4ab-4ac-4bc
leeyiu said:how do you know that (-ab-bc-ca) is a positive numbers?
Could you please try the hint you've already been given...?leeyiu said:Can you five my some more hints?
leeyiu said:alright I'll show you my work
(c-a)x^2-2(a-b)x+(b-c)=0
discriminant=
4(a-b)^2 -4(c-a)(b-c)=
4a^2 -8ab +4b^2 + 4c^2 -4cb-4ca-4ab =
4a^2 +4b^2 +4c^2 - 4cb -4ca -4ab
= 2[(a^2 + b^2 - 2ab) + (b^2 + c^2 - 2bc) + (c^2 + a^2 - 2ac)]
= prove this is a positive number and you are done